Design And Manufacture Of Automated Home Lighting Regulatory Devices With Iteaduino Microcontroller Atmega 328p-Based LDR - Muhammad Andi; Alexius Ulan Bani; Fifto Nugroho (Yayasan Bina Internusa Mabarindo, 2022)
Automatic lighting aims to facilitate work, generally lights use a switch with the principle of an on-off switch. To overcome this, it is necessary to manufacture a tool that functions as a lighting regulator that is able to adjust to certain conditions in a room. Conducting observations accurately, the literature study method collects data related to the topic. Hardware design process and how the tool works. Software is a systematic process program that functions as a tool command, tool testing by implementing tool work. The result of the research is that the tool can work well as desired and the power is stable for each component used.